The Gut Microbiota and Associated Metabolites Are Altered in Sleep Disorder of Children With Autism Spectrum Disorders - Hua, Xueying; Zhu, Jiang; Yang, Ting; Guo, Min; Li, Qiu; Chen, Jie; Li, Tingyu (Frontiers in Psychiatry, 2020)
Objectives: This study was designed to investigate the alteration of gut microbiota and its metabolites and correlation with core symptom in sleep problems of children with autism spectrum disorders (ASD). Methods: One hundred and twenty children with ASD diagnosed by the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria were enrolled in our study. The Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Social Responsiveness Scale (SRS) were used to assess the symptoms, and the Children Sleep Habits Questionnaire (CSHQ) was evaluated sleep problems in children with ASD. The 120 children were divided into sleep disorder group (n=60) and non sleep disorder group (n=60) according to the standard of CSHQ. Illumina MiSeq for 16S rRNA genes was detected to compare the differences in gut microbiota and metabolomics was analyzed the metabolites of gut microbiota. Results: The SRS and CARS scores of the sleep disorder group were significantly higher than those of the non sleep disorder group (P<0.05). The abundance of butyrate-producing bacteria Faecalibacterium and Agathobacter were reduced significantly in sleep disorder group (P<0.05), which abundances were negatively related with CSHQ scores (P=0.007, P=0.014), and the abundance of Agathobacter was also negatively associated with the Language score in ABC (P=0.044). Furthermore, the levels of 3-Hydroxybutyric acid and melatonin were significantly lower (P<0.05) and the serotonin level was statistically higher (P<0.05) in the sleep disorder group. The 3-Hydroxybutyric acid level was positively associated with Faecalibacterium abundance (P=0.000), and melatonin was positively associated with abundances of Faecalibacterium (P=0.036) and Agathobacter (P=0.041). We further found negative correlations between 3-Hydroxybutyric acid and CSHQ (P=0.000) and CARS (P=0.009), between melatonin and CSHQ (P=0.002) and sensory score in ABC and (P=0.021), whereas a positive correlation between serotonin and CSHQ (P=0.002) and sensory score in ABC (P=0.025). Conclusions: The ASD children with sleep disorder exhibit declines in abundances of Faecalibacterium and Agathobacter, as well as decreases in the levels of 3-Hydroxybutyric acid and melatonin, and an increase in serotonin. These maybe aggravate sleep problems and core symptoms in children with ASD.